An epidemiological study of the perimenopausal and menopausal health problems in women living in an urban area of Mumbai, Maharashtra - Jadhav, Ashwin; Bavaskar, Yogita (International Journal Of Community Medicine And Public Health, 2017)
Background: Menopause is a transitional period of changing role and status of women from reproductive to post reproductive age. It occurs due to decrease in level of oestrogen, which leads to multiple menopausal symptoms. The objectives were to study the health and psychological problems associated with menopause and to study the relation of health and psychological problems with age, marital status, socio-economic status, parity and tobacco use. Methods: A cross-sectional study was carried out amongst women in the age group of 40 to 50 years during the period of February 2012 to February 2013 to know the epidemiological profile of peri and postmenopausal women. The study information of the women was collected by personal interview technique by home visits. Results: The average age at menopause amongst the study subjects was 45 yrs. The most common problem faced by the respondents was somatic symptoms. Among those the most common was muscle joint pains 65.1%. This study found significant association in marital status, parity, tobacco chewing and increased the occurrence of menopausal symptoms. Conclusions: There is a high burden of menopausal symptoms in women and the menopausal symptoms are affected by various socio-demographic factors like marital status, parity, tobacco chewing.